PERKEMBANGAN CORAK PENAFSIRAN AL-QUR’AN DARI PERIODE KLASIK SAMPAI MODERN - Muhamad Ibtissam Han; Topikurohman (Institut PTIQ Jakarta, 2020)
This article will explain the development of the style of interpretation of the Koran from the classical period to the modern period. The authors use the literature research model (literature study) by reading books on interpretations from scholars and commentaries of scholars. Broadly speaking, the Classical period has many agreed-upon models of interpretation based on tradition and many uses of Islamic sources also support the linguistic aspect. While in the modern period emerged against the Old traditions ranging from the use of israiliyat tradition, the authority of the prophet, linguistic to the combination of the tradition of Western positivism thinking that illustrates various interpretations in the modern period with the exchange of mystical concepts and primitive concepts, also helped realize the discussions that support religion drocal.